Extracellular vesicle-microRNAs mediated response of bovine ovaries to seasonal environmental changes - Ahmed Gad; Kamryn Joyce; Nico Graham Menjivar; Daniella Heredia; Camila Santos Rojas; Dawit Tesfaye; Angela Gonella-Diaza (BMC, 2023)
Abstract Background Among the various seasonal environmental changes, elevated ambient temperature during the summer season is a main cause of stress in dairy and beef cows, leading to impaired reproductive function and fertility. Follicular fluid extracellular vesicles (FF-EVs) play an important role in intrafollicular cellular communication by, in part, mediating the deleterious effects of heat stress (HS). Here we aimed to investigate the changes in FF-EV miRNA cargoes in beef cows in response to seasonal changes: summer (SUM) compared to the winter (WIN) season using high throughput sequencing of FF-EV-coupled miRNAs. In addition to their biological relevance, the potential mechanisms involved in the packaging and release of those miRNAs as a response to environmental HS were elucidated. Results Sequencing analysis revealed that an average of 6.6% of the EV-RNA mapped reads were annotated to bovine miRNAs. Interestingly, miR-148a, miR-99a-5p, miR-10b, and miR-143 were the top four miRNAs in both groups accounting for approximately 52 and 62% of the total miRNA sequence reads in the SUM and WIN groups, respectively. A group of 16 miRNAs was up-regulated and 8 miRNAs were down-regulated in the SUM compared to the WIN group. Five DE-miRNAs (miR-10a, miR-10b, miR-26a, let-7f, and miR-1246) were among the top 20 expressed miRNA lists. Sequence motif analysis revealed the appearance of two specific motifs in 13 out of the 16 upregulated miRNAs under HS conditions. Both motifs were found to be potentially bonded by specific RNA binding proteins including Y-box binding proteins (YBX1 and YBX2) and RBM42. Conclusion Our findings indicate that FF EV-coupled miRNA profile varies under seasonal changes. These miRNAs could be a good indicator of the cellular mechanism in mediating HS response and the potential interplay between miRNA motifs and RNA binding proteins can be one of the mechanisms governing the packaging and release of miRNAs via EVs to facilitate cellular survival.